Finite symmetric trilinear integral transform of distributions. Part II - G. L. Waghmare; S. V. More (International Journal of Mathematics and Mathematical Sciences)
The finite symmetric trilinear integral transform is extended to distributions by using quite different technique than Zemanian (1968) and Dube (1976) and an inversion formula is established using Parseval's identity. The operational calculus generated is applied to find the temperature inside an equilateral prism of semi-infinite length.